2018
DOI: 10.1097/md.0000000000011996
|View full text |Cite
|
Sign up to set email alerts
|

Mulberry leaf extract reduces the glycemic indexes of four common dietary carbohydrates

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 39 publications
2
32
0
1
Order By: Relevance
“…A number of different plant extracts have been shown to reduce postprandial glycemia or GI of common carbohydrates and carbohydrate-rich foods. Wang et al reported that consumption of mulberry leaf extracts reduced the overall glycemic response, peak glucose concentrations at 30 min, and GI of glucose by 8.2% [25]. In our study, supplementation with FFE reduced GI to a greater extent (13%–25%) compared to mulberry leaf extracts.…”
Section: Discussionsupporting
confidence: 45%
“…A number of different plant extracts have been shown to reduce postprandial glycemia or GI of common carbohydrates and carbohydrate-rich foods. Wang et al reported that consumption of mulberry leaf extracts reduced the overall glycemic response, peak glucose concentrations at 30 min, and GI of glucose by 8.2% [25]. In our study, supplementation with FFE reduced GI to a greater extent (13%–25%) compared to mulberry leaf extracts.…”
Section: Discussionsupporting
confidence: 45%
“…Considerable human studies have further elucidated the hypoglycemic effects of mulberry leaf extract in healthy participants, with fewer studies on prediabetes and T2DM [71][72][73]129,[131][132][133][134][135][136][137][138][139]. Liu and colleagues (2020) investigated the acute hypoglycemic effects of an extract mixture of mulberry leaf and white kidney bean in participants with IFG [74].…”
Section: White Mulberry Leafmentioning
confidence: 99%
“…[27] Penggunaan DNJ sebagai antiobesitas dan antihiperglikemik diketahui memiliki efek samping yang lebih sedikit dibandingkan dengan acarbose, obat anti-diabetik yang juga zat penghambat enzim α-glukosidase yang telah disarankan dalam pedoman di banyak negara yang memiliki efek samping pada pencernaan seperti diare dan perut kembung. [28] Beberapa studi menunjukkan DNJ tidak memiliki potensi toksiksitas maupun efek mutagenik yang merugikan bila dikonsumsi dalam jangka panjang. [29] Iminosugar DNJ sudah digunakan dan memiliki tingkat keamanan dan tolerabilitas dalam pengobatan penyakit Gaucher yang diakibatkan lysosomal storage disorder maupun non-insulin-dependent diabetes.…”
Section: Bahasan Patogenesis Infeksi Virus Dengueunclassified